Identification of Key Residues in the NisK Sensor Region for Nisin Biosynthesis Regulation - Ge, Xiaoxuan; Teng, Kunling; Wang, Jian; Zhao, Fangyuan; Zhang, Jie; Zhong, Jin (Frontiers in Microbiology, 2017)
Histidine kinase (HK) NisK is well known to sense lantibiotic nisin for regulating the biosynthesis of nisin. NisK possesses two trans-membrane segments and a large extracellular region and nisin contains 34 amino acids with five lanthionine rings. Unlike most peptide sensing HK with multi trans-membrane segments, NisK is a representative of a group of rarely reported HK that sense peptide as ligand. To reveal how NisK senses nisin molecule to regulate nisin biosynthesis, we constructed a reporter Lactococcus lactis strain with nisRK constitutively expressed and a reporter gene lacZ expressed under the control of promoter PnisA. We showed that the extracellular region of NisK was involved in recognizing nisin. Conserved residues in this group of HK were found in the extracellular region of NisK and mutagenesis of these residues in the reporter strain revealed that several hydrophobic residues including two aromatic residues are crucial for NisK sensing nisin and regulating nisin biosynthesis. Substitutions of hydrophobic regions in NisK extracellular domain showed that the first strand that was rich of hydrophobic amino acids was involved in regulating nisin biosynthesis. A negatively charged residue in the first βstrand also contributed to nisin biosynthesis. Protein binding analyses demonstrated that nisin could not interact with key NisK mutants, indicating these site in the extracellular region of NisK was involved in recognizing nisin.